Corporate Social Responsibility and Financial Performance: Evidence from India’s IT Sector - Kudumula, Umamaheswara Reddy; Bhandari, Nikhil (Journal of Global Economy, Business and Finance, 2025)
The main objective of the study is to assess the impact of Corporate Social Responsibility (CSR) spend on the financial performance of the leading five Indian IT sector companies and compare their respective financial outcomes. To achieve this research aim, a comprehensive dataset of Indian IT sector firms is gathered, containing financial performance metrics and CSR - related indicators for the period spanning from 2018 - 19 to 2022 - 23. The financial performance metrics consist of crucial indicators such as Return on Assets (ROA), Profitability, Turnover, and Liquidity. The results of this investigation are expected to provide valuable insights into how CSR impacts the financial performance of Indian IT companies. These findings could serve as essential guidance for policymakers and offer strategic insights for businesses contemplating CSR initiatives. Furthermore, the study's examination of the link between CSR, even amidst the critical time of COVID - 19, and its impact on financial performance may aid stakeholders and investors in making informed investment decisions.